Mycotic Aneurysm in the Aortoiliac Area – Current Options for Treatment - Krejcí, M.; Staffa, R.; Dvorák, M.; Holub, R.; Vojtíšek, B.; Kríž, Z.; Konecný, Z.; Bucek, J. (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2015)
Background: Infection represents a less frequent cause for the development of an abdominal aortic aneurysm. The diagnosis is associated with a high risk of rapir progression and rupture. Case Reports: Case 1 is a female operated on urgently for a ruptured mycotic aneurysm of the abdominal aorta. After resection of the aneurysm, we performed in situ replacement using a rifampicin-soaked vascular prosthesis. In case 2, an asymptomatic aneurysm of the right iliac artery was treated by endovascular implantation of a stent-graft. Both patients were treated with antibiotics concurrently and are still alive. Discussion: The discussion deals with the up-to-date treatment modalities for mycotic aneurysms in the aorto-iliac region. The indication criteria must be adjusted individually. Conclusion: The prognosis of patients with a mycotic aneurysm depends particularly on an early diagnosis.
Keywords: mykotische Aneurysma; in situ Prothese; Stentgraft; autologe Vena femoralis